Towards marine biorefineries: Selective proteins extractions from marine macroalgae Ulva with pulsed electric fields. (October 2016) - Polikovsky, Mark; Fernand, Francois; Sack, Martin; Frey, Wolfgang; Müller, Georg; Golberg, Alexander
Abstract: Macroalgae are potential feedstock for biorefineries. However, integration of macroalgae into biorefinery network requires new processing technologies that will lead to energy efficient and zero waste conversion of macroalgae biomass into food, chemicals and fuels. Here we report on the selective extraction of proteins from green macroalgae from Ulva genus by electroporation with energy efficient pulsed electric field (PEF) process. We show that application of 75 pulses with an average electric field strength of 2.964 ± 0.007 kV cm − 1, and pulse duration 5.70 ± 0.30 μs, delivered at approximately 0.5 Hz, combined with hydraulic pressing of the treated samples for 5 min with force of 45 daN cm − 2 led to the total protein concentration of 59.13 ± 3.82 μg mL − 1 in the extracted juice. The final temperature of the extracted juice was 35.50 ± 2.02 °C. The energy consumption of the process is 251 ± 3 kWh kg − 1 of protein. We show that PEF process is selective and its extraction efficiency and damage are protein specific. Highlights: Pulsed electric field protein extraction Protein extraction from macroalgae Ulva Energy efficient marine biorefineries Identification of proteins extracted with pulsed electric fields from macroalgae Ulva